The linkage between income distribution and clean energy investments: Addressing financing cost - Nadia Ameli; Daniel M. Kammen (Fondazione Eni Enrico Mattei (FEEM), 2012)
With a focus on alternative methods for accelerating clean energy policy adoption, this study introduces an innovative financing scheme for renewable and energy efficiency deployment. Financing barriers represent a notable obstacle for energy improvements and this is particularly the case for low-income households. Limited access to credit, due to socio-economic status and the lack of guarantees, are key issues related to financing barriers. Implementing a policy such as PACE - Property Assessed Clean Energy - allows for the provision of up-front funds for residential property owners to install electric and thermal solar systems and make energy-efficiency improvements to their buildings. This paper will inform the design of better policies tailored to the creation of the appropriate conditions for such investments to occur, especially when the lack of access to capital tends to stall them.
Keywords: Q42; Q55; 330; Financing Barriers; Energy Efficiency; Solar PV; Energy Investments